Analisis Efektivitas Layanan GOOL (Dukcapil Go Online) Dalam Mempercepat Penerbitan Akta Kelahiran Sebagai Upaya Peningkatan Pelayanan Publik (Studi Pada dinas kependudukan dan Catatan Sipil Kota Probolinggo) - Ningsih, Ayu; Mubaroq, Husni; Rahmadi, Andhi Nur (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
This study examines the effectiveness of the GOOL (Dukcapil Go Online) service in accelerating the issuance of birth certificates at the Population and Civil Registration Office of Probolinggo City. GOOL is a digital-based civil administration service innovation that allows residents to process civil documents without visiting the office in person. This study employed a descriptive qualitative method, with data collected through in-depth interviews, observation, and documentation. Effectiveness indicators were based on Campbell's (2014) theory, covering: program success, goal achievement, community satisfaction, and overall objective attainment. The findings indicate that the GOOL service is generally effective in expediting birth certificate issuance. Supporting factors include collaboration with healthcare facilities (Indonesian Midwives Association and hospitals), an integrated 3-in-1 service program, and adequate technological infrastructure. Inhibiting factors include technical difficulties during document uploads, unstable internet connections, and limited digital literacy among some residents.